Effect of two behavioural 'nudging' interventions on management decisions for low back pain: a randomised vignette-based study in general practitioners. Issue 7 (19th November 2018) - Soon, Jason; Traeger, Adrian C; Elshaug, Adam G.; Cvejic, Erin; Maher, Chris G; Doust, Jenny A; Mathieson, Stephanie; McCaffery, Kirsten; Bonner, Carissa
Abstract : Objective: 'Nudges' are subtle cognitive cues thought to influence behaviour. We investigated whether embedding nudges in a general practitioner (GP) clinical decision support display can reduce low-value management decisions . Methods: Australian GPs completed four clinical vignettes of patients with low back pain. Participants chose from three guideline-concordant and three guideline-discordant (low-value) management options for each vignette, on a computer screen. A 2×2 factorial design randomised participants to two possible nudge interventions: 'partition display' nudge (low-value options presented horizontally, high-value options listed vertically) or 'default option' nudge (high-value options presented as the default, low-value options presented only after clicking for more). The primary outcome was the proportion of scenarios where practitioners chose at least one of the low-value care options. Results: 120 GPs (72% male, 28% female) completed the trial (n=480 vignettes). Participants using a conventional menu display without nudges chose at least one low-value care option in 42% of scenarios. Participants exposed to the default option nudge were 44% less likely to choose at least one low-value care option (OR 0.56, 95%CI 0.37 to 0.85; p=0.006) compared with those not exposed. The partition display nudge had no effect on choice of low-value care (OR 1.08, 95%CI 0.72 to 1.64; p=0.7). There was no interaction between the nudges (OR 0.94, 95% CI 0.41 to 2.15; p=0.89). Interpretation: A default option nudge reduced the odds of choosing low-value options for low back pain in clinical vignettes. Embedding high value options as defaults in clinical decision support tools could improve quality of care. More research is needed into how nudges impact clinical decision-making in different contexts.